Bone formation following sinus grafting with an alloplastic biphasic calcium phosphate in Lanyu Taiwanese mini‐pigs. Issue 1 (30th October 2019) - Hung, Chao‐Chien; Fu, Earl; Chiu, Hsien‐Chung; Liang, Huang‐Chien
Abstract: Background: To evaluate the new bone formation after grafting with a synthetic biphasic calcium phosphate in sinuses with minimal bone height, the alloplastic and xenograft materials were compared after grafting into Lanyu Taiwanese mini‐pig sinuses via split‐mouth design. Methods: In six mini‐pigs, synthetic hydroxyapatite/tricalcium phosphate (HA/TCP) particles were inserted into one of the sinus cavities using the extra‐oral approach, where deproteinized bovine bone mineral (DBBM) particles were placed contralaterally. Fluorescent bony labels of Alizarin and Calcein green were delivered at weeks 4 and 8, respectively. Animals were sacrificed at week 12 and the augmented tissues were evaluated by cone‐beam computed tomography, microcomputed tomography, and histology. Results: By radiographic examination, the mean thicknesses of sinus cortexes for DBBM and HA/TCP groups were similar (0.35 versus 0.38 cm) and the mean volumes augmented were also indifferent (1.29 versus 1.64 cm 3 ). The distributions of bones, residual particles, and non‐mineralized tissues in augmented masses between groups were undistinguishable. Under microscopy, however, macroporosities of osteons were filled with HA/TCP residual particles, whereas the newly formed bones lay on top of DBBM particle surfaces. Although the mineral deposition rates between groups were indifferent, the mean labeled surface in the HA/TCP group was significantly greater than those in the DBBM group at week 4 (35.16% versus 14.00% for HA/TCP and DBBM, respectively) but less than that at week 8 (19.33% versus 39.16%, respectively). Conclusion: Sinus augmentation with synthetic HA/TCP and DBBM exhibited similar effectiveness in new bone formation.